Supplier perceptions of dependencies in supplier–manufacturer relationship - Hassan, Mohamad Ghozali; Razalli, Mohd Rizal; Abdullah, Rohani; Johari, Nor Azmi; Othman, Abdul Aziz (2013)
The purpose of this research is to explore the relationship between supplier’s dependency and the relationship orientation of supplier-manufacturer relationship. The main tools of data collection instrument used was a questionnaire which was administrated to a total sample of 210 managers is classified by job title and respondents are also classified by their job functions are corporate executives, purchasing, manufacturing or production, material, and operation from Malaysia electrical and electronic manufacturing industry.The response rate was 26% while 96% were usable questionnaires. Sample selection was based on random sampling.The data were analyzed using mean, standard deviation and correlation between independent and dependent variables. The analyses involved statistical methods such as reliability and validity tests and multiple regressions. The findings show that the supplier perceives dependency has a significant relationship with relationship orientation statically.